2004
DOI: 10.1161/01.cir.0000138390.81640.54
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Human Copper/Zinc Superoxide Dismutase (SOD1) Suppresses Ischemia–Reperfusion Injury and Subsequent Development of Graft Coronary Artery Disease in Murine Cardiac Grafts

Abstract: Background-Ischemia-reperfusion injury is an important risk factor for graft coronary artery disease (GCAD). We hypothesized that overexpression of SOD1 in donor hearts would suppress ischemia-reperfusion injury and thereby reduce GCAD. Methods and Results-In one series, donor hearts of C57BL/6 (H-2 b ) transgenic mice overexpressing human SOD1 or C57BL/6 wild-type mice were heterotopically transplanted into C57BL/6 recipients and procured after 4 hours of reperfusion (nϭ6 each). Superoxide, TNF-␣, and MCP-1/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 31 publications
2
56
0
Order By: Relevance
“…46 Intriguingly, ischemia-reperfusion injury is also a well-known alloantigen-independent risk factor for acute allograft rejection and subsequent cardiac allograft vasculopathy. 47,48 Although not directly tested in this study, other IL-17-producing cells likely participate during the pathogenesis, because the acute allograft rejection noted in ␥␦ T cell-deficient mice was not as severe as WT controls. These findings support potential development of immunosuppressive agents directed at ␥␦ T cells.…”
Section: Discussionmentioning
confidence: 87%
“…46 Intriguingly, ischemia-reperfusion injury is also a well-known alloantigen-independent risk factor for acute allograft rejection and subsequent cardiac allograft vasculopathy. 47,48 Although not directly tested in this study, other IL-17-producing cells likely participate during the pathogenesis, because the acute allograft rejection noted in ␥␦ T cell-deficient mice was not as severe as WT controls. These findings support potential development of immunosuppressive agents directed at ␥␦ T cells.…”
Section: Discussionmentioning
confidence: 87%
“…Caspase-3, the major form of caspase, is served as an "apoptotic executor" that cleaves substrates, such as ploy(AdP-ribose) polymerase, finally leading to DNA fragmentation and cell loss. 28) A remarkable elevation of caspase-3 was previously found in isoproterenol-induced acute myocardial infarction in Wistar rats. 24) our current study reported the consistent alteration of caspase-3 in infarcted hearts and meanwhile baicalin treatment obviously decreased caspase-3 expressions as well as its activity in the rats undergoing acute myocardial infarction.…”
Section: Effects Of Baicalin On the Caspase-3 Protein And Mapk Cascadmentioning
confidence: 84%
“…Excess H 2 O 2 is normally reduced to water by catalase or glutathione peroxidase, preventing the production of hydroxyl radicals. It has been shown that SOD1 plays an important role in suppressing superoxide generation, apoptosis, and the inflammatory response in oxidative stress-related cardiac diseases (Mital et al 2011;Tanaka et al 2004;Chen et al 2000;Land et al 1994).…”
Section: Resultsmentioning
confidence: 99%